Zé Maria from Tomé Camp: socio-environmental struggles and knowledge that are being built in Chapada from Apodi - CE (Research, Society and Development, 2020)
In this research, we aim to identify the educational phenomenon expressed in the struggle of the socio-historical subjects of the Zé Maria from Tomé / Chapada from Apodi-Ceará Camp, evaluating the dialogues that are built between the popular knowledge of the campers and the academic academic groups in the exchange of knowledge that enable a process of awareness and unveiling of reality. The methodology consisted of direct observation of experiences of non-formal education in social movements, in the period between 2014 and 2019. For this, we developed a qualitative study, of the descriptive and explanatory type from field research, referenced in Freire (2019), Brandão (2007) and Gohn (1995 and 2001). We reflected on the socio-environmental struggles of Chapada from Apodi and its implication in the formation of the critical conscience of campers. As a result of the field research, we could perceive principles of social organization, struggle and resistance, from political awareness, allowing us to conclude that these subjects have been looking for forms of resistance and organization to overcome the adversities found in daily life, in the perspective of breaking with the contradictory development of capital in that territory, articulating these social practices to the construction of knowledge with university groups.